2019
DOI: 10.1016/j.cell.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Is a Natural Suppressor of RLR Signaling by Targeting MAVS

Abstract: RLR-mediated type I IFN production plays a pivotal role in elevating host immunity for viral clearance and cancer immune surveillance. Here, we report that glycolysis, which is inactivated during RLR activation, serves as a barrier to impede type I IFN production upon RLR activation. RLR-triggered MAVS-RIG-I recognition hijacks hexokinase binding to MAVS, leading to the impairment of hexokinase mitochondria localization and activation. Lactate serves as a key metabolite responsible for glycolysis-mediated RLR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
327
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(381 citation statements)
references
References 53 publications
7
327
1
Order By: Relevance
“…Lactate has long been known as a negative regulator of antitumor immunity. 31,32 For example, lactate can induce TAMs to differentiate into an M2-like phenotype by activating HIF-1α, thus promoting tumor development. 31 Here, we found that lactate could stimulate the translocation of Ap-2α from the cytoplasm to the nucleus, thus potentiating the Elk-1/Sirpα axis-mediated "don't eat me" signal.…”
Section: Discussionmentioning
confidence: 99%
“…Lactate has long been known as a negative regulator of antitumor immunity. 31,32 For example, lactate can induce TAMs to differentiate into an M2-like phenotype by activating HIF-1α, thus promoting tumor development. 31 Here, we found that lactate could stimulate the translocation of Ap-2α from the cytoplasm to the nucleus, thus potentiating the Elk-1/Sirpα axis-mediated "don't eat me" signal.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with influenza recruited in the present study were confirmed as being infected with H1N1 virus by qPCR. PBMCs were isolated using standard Ficoll gradient centrifugation from the peripheral blood of either infected C labeling of UDP-GlcNAc from U-13 C 6 -glucose was detected from cell lysates using nuclear magnetic resonance (NMR) spectroscopybased metabolomics analysis (16,17). Briefly, samples were dried and on September 1, 2020 http://advances.sciencemag.org/ Downloaded from then reconstituted using phosphate buffer in 100% D 2 O with 500 mM TMSP as a chemical shift reference.…”
Section: Clinical Samplesmentioning
confidence: 99%
“…Reprogramming cellular metabolic activities has recently been demonstrated to play a critical role in the activation of the immune system and hyperinflammation (15). A widely accepted concept is that embedded in immune cell physiology are metabolic pathways and metabolites that not only provide energy and substrates for growth and survival but also direct effector functions, differentiation, and gene expression (16,17). Previous studies reported increased glucose uptake and utilization in immune cells, serving as a hallmark feature of acute inflammation (18).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, lactate restoration reverses increased IFN production caused by lactate deficiency. LDHA inactivation and subsequent lactate reduction, using pharmacological and genetic approaches, increases type I IFN production and protects mice from viral infection (W. Zhang et al, ).…”
Section: Lactate Modulates Immune Cell Functionsmentioning
confidence: 99%